The Solvability of the Initial-Boundary Value Problems for a Nonlinear Schrödinger Equation with a Special Gradient Term - Yagub, G.; Ibrahimov, N.S.; Zengin, M. (Журнал математической физики, анализа, геометрии, 2018)
In this paper, the initial-boundary value problems for the two-dimensional nonlinear Schrödinger equation with a special gradient term with purely imaginary coefficients in the nonlinear part, when the coefficients of the equation are measurable bounded functions, are considered. The existence and uniqueness of solutions of the first and second initial-boundary value problems is proved almost everywhere. У статтi розглядаються початково-крайовi задачi для двовимiрного нелiнiйного рiвняння Шредiнгера iз спецiальним градiєнтним членом з чисто уявними коефiцiєнтами в нелiнiйнiй частинi, коли коефiцiєнти рiвняння є вимiрними обмеженими функцiями. Доведено iснування i єднiсть розв язкiв першо i друго початково-крайово задачi майже скрiзь.